ANALISIS KEBIJAKAN PEMBELAJARAN PENDIDIKAN ISLAM ANAK USIA DINI - Fu`ad Arif Noor (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
Level of education, amount of incentive and the level of competence of teachers/caretakers three significantly influenced by the status of civil servant teachers/PNS on the quality of children's ideal, the status of civil servants/PNS for early childhood education programs/PIAUD should have the qualifications and competence yangt accordance with minimum service standards so that it has a higher chance to create quality children's ideal , Level of education, amount of incentive and the level of competence of teachers/caretakers three significantly influenced by the status of volunteer teachers to the quality of children's ideal, voluntary status for early childhood education programs/PIAUD should have the qualifications and competence yangt accordance with minimum service standards so that it has a higher chance to create quality children's ideal , but almost all providers of early childhood education conducted by both the foundations and the community pay less attention to the qualifications and competence His nurse, so it looks only at who has the time to become caretakers. It has alarming effects, seen from the perspective of educational administration, the ideal child's success into question, and generation like what 20 years to come. There is some education that shall be given to early childhood include: grateful, tauhid (with mengadzankan), physical education (strong physical), health, and intelligence.